TTIP and public procurement: going beyond the tip of the iceberg - Cernat, Lucian; Kutlina-Dimitrova, Zornitsa (Brussels, 2016)
" Trade negotiations involving international public procurement rules are on the rise, stimulating a growing interest in having a clear picture of the economic stakes involved, including the current level of international openness. A recent paper published by the European Centre for International Political Economy (Messerlin, 2016) made an attempt to provide a range of estimates for the EU and the US and found relatively low rates of import penetration. This analytical approach, however, looked only at the ‘tip of the procurement iceberg’, as the data used covered primarily only one modality of international procurement (direct cross-border), which is not the main avenue for international government procurement. Other modalities, such as procurement from foreign subsidiaries established in Europe, account for much more. Such an approach therefore ignores the main modalities through which foreign firms win EU contracts. Once these other main procurement modalities are taken into account, EU openness in procurement is much higher. Comparable data across all modalities do not yet exist for the US, but we do have clear evidence that the US has introduced the largest number of protectionist procurement measures since 2008 affecting all modalities for international procurement.